MANAGING WORK PRODUCTIVITY THROUGH GLOBAL COMPETENCE - Bambang Haryanto; Candra Darmawan (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
This research was conducted to determine the role of global competence in practice in the industrial world on work productivity with motivation as a moderating variable that influences it with this type of applied research using quantitative methods Partial Least Square Structural Equation Model (PLS-SEM) explaratory prediction using SmartPLS software , the results of the research In this case, there is a significant effect between Global Competence on Work Productivity, while for the motivation variable as a moderating Global Competence on work productivity, it has a very small effect, namely 0.817 but has no effect at a significant level of 0.005.